Calcifying epithelial odontogenic tumours: Collaborative study of 32 cases and review of literature. (9th September 2018) - de Arruda, José Alcides A.; Abreu, Lucas G.; Silva, Leni Verônica de O.; Schuch, Lauren F.; Monteiro, João Luiz G. C.; Arantes, Diego Antônio C.; da Costa, Adriana Aparecida S.; Nóbrega, Kaio Heide S.; Vasconcelos, Ana Carolina U.; de Andrade, Bruno Augusto B.; Romañach, Mario José; Sobral, Ana Paula V.; et al.
Abstract: Objectives: To analyse the occurrence of calcifying epithelial odontogenic tumours (CEOT) based on biopsy records from different Brazilian geographic regions and to contrast the data with a review of the literature. Materials and methods: A 2‐step study was conducted. Step 1 consisted of a collaborative study of biopsies obtained from 1953 to 2017 at six Brazilian oral and maxillofacial pathology centres. Evaluation of 86, 268 biopsy records was performed. Demographic and histopathological diagnosis data were assessed. In Step 2, a review of the literature of case reports and cases series of CEOT identified across five electronic databases was conducted. Results: In the collaborative study, 32 cases of CEOT were evaluated. This figure represented 0.03% of the oral and maxillofacial lesions and 1.7% of all odontogenic tumours across the centres. Women in the fourth decade of life were more affected. CEOT occurred more in the mandible than in the maxilla (ratio 1.9:1). The review of the literature showed that Asian individuals were more affected by this neoplasm. Conclusions: Useful knowledge on the epidemiology, treatment and follow‐up of CEOT has been provided. Demographic data and clinical features of the cases presented in this collaborative study were quite similar to those of studies reported worldwide.